Tutor Competencies in Inclusive Education: Specifics of Professional Training Curricula - E.V. Samsonova; Y.A. Bystrova; A.Yu. Shemanov; E.N. Kutepova (Moscow State University of Psychology and Education, 2022)
The article provides a comparative analysis of the features of readiness and ability for tutor support as components of professional competencies of students of higher and secondary vocational education, as well as working tutors. The sample of this study is represented by 159 respondents - 67 working tutors, 33 undergraduates in the direction of higher education "Psychological and pedagogical education", 59 respondents, of which 28 undergraduates of higher education (direction "Social work") and 31 students of secondary vocational education (specialty "Social work"). The study was carried out using the scales developed by us to assess professional competencies for tutor support in the context of inclusive education. The answers to the questionnaire were collected remotely using the "Anketolog" system and processed statistically using the SPSS Statistics 18.0 program. In all groups of respondents, the revealed statistically significant correlations between the scales corresponded to the connections of similar scales used in international studies. It is shown that students of the social direction are more ready to implement tutor functions related to the actualization of the subject position of students, and students of the psychological and pedagogical orientation of the programs are more familiar with the knowledge, methods of work that ensure the creation of special conditions for education for the child as an object of psychological pedagogical support. It is concluded that when preparing graduates of secondary vocational and higher education, it is necessary to balance the development by graduates of competencies aimed at mastering the methods and techniques of creating special educational conditions for students with disabilities, and competencies associated with methods and techniques that support their active, involved participation in the process of education, the harmonious combination of which makes up the specifics of tutor support in the context of inclusion.